Neurenteric Cysts of the Cerebellopontine Angle - Roder, Constantin; Ebner, Florian H.; Schuhmann, Martin U. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Neurenteric cysts in the central nervous system are rare developmental malformations. Usually the cysts are located ventral to the high thoracic or low cervical spinal cord. Only a few cases of intracranial neurenteric cysts have been reported in the literature to date. We report two cases of intracranial neurenteric cysts in the cerebellopontine angle with totally different radiographic, macroscopic, and microscopic appearance. As seen in these cases, the imaging spectrum of neurenteric cysts can be diverse, including malignancy-suspecting partial rim-enhancement or low-grade glioma features. Microsurgical therapy should include endoscopic assistance to ensure complete removal of cyst content.
Keywords: neurenteric cyst; endodermal cyst; posterior fossa; cerebellopontine angle